Micropower design of energy harvesting based on piezoelectric transducer array circuit - Juanda, Enjang Akmad; Hakim, Nurul Fahmi Arief; Sarosa, Moechammad; Saputra, Dede Irawan; Azhima, Silmi Ath Thahirah Al; Qibtiya, Mariya Al (Institute of Advanced Engineering and Science, 2024)
This article reveals the conceptualization and implementation of energy harvesting system that utilize piezoelectric arrays within environments marked by elevated ambient noise levels. The selected methodology involves conducting an empirical study where the system is introduced into a room with pronounced ambient noise. A series configuration is adopted for assembling the piezoelectric sensors. For this particular experiment, 36 piezoelectric sensor units were arranged, each equipped with a voltage doubler circuit, aiming to harness a specific micropower energy threshold. The experimental results validate the successful development of an energy harvesting mechanism employing a piezoelectric array within a noisy setting. Notably, the device functions optimally at a frequency of 250 Hz. Additionally, a series of controlled experimental tests were executed at a sound level of 95.8 dBA to assess the efficacy of the piezoelectric array. Measurements taken at the voltage doubler output reveal that the device achieves its peak output signal at 3.32 Vpp and 50.42 Hz. The maximum attainable direct current (DC) voltage stands at 1 Volt, complemented by a current of 0.45 mA.